TECHNOLOGIES FOR THE FORMATION OF INDIVIDUAL TRAINING IN DISTANCE EDUCATION OF DOCTORS AND PHARMACISTS - Mintser, O. P.; Gabovych, A. G.; Koshоva, S. P. (Medical Informatics and Engineering, 2020)
Background. The questions of formation of individual educational trajectory in the system of postgraduate training of doctors and pharmacists are considered. It is emphasized that in spite of the further processes of university education opening, creation of remote knowledge transfer platforms, formation of an individual educational plan is not carried out. There are no mathematical estimates for learning optimization. Materials and methods. Results. It becomes important to determine the basic principles of forming an individual educational trajectory. It is concluded that the construction of an individual educational trajectory of doctors and physicians should be completed at the bachelor's stage. Conclusion. It is emphasized that the portfolio, as the primary document of the doctor, should contain a technological map of education, with mandatory inclusion in the process of teaching skills related to patient-centered approach, communication principles and increased content of behavioral and social sciences.